1969
DOI: 10.1530/acta.0.0600555
|View full text |Cite
|
Sign up to set email alerts
|

A Modification of the Pigeon Crop Sac Assay for Lactotrophic Hormone Determinations by Means of the Addition of Prednisolone

Abstract: For LTH-determination in biological material without preliminary extraction procedures the pigeon crop sac assay, performed by the micro-method of Grosvenor & Turner (1958), and modified by the addition of prednisolone to the standard or test material was used. Serum samples of lactating women caused no inflammations of the skin of the pigeons, and the crop sacs hardly showed any signs of inflammation. Reaction sites could be measured more easily, and the LTH activities in the plasma were about 3 times hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Apostolakis, 1968;Herlyn, Jantzen, Flaskamp, Hoffmann & von Berswordt-Wallrabe, 1969 Preliminary experiments showed that the storage of human pituitary glands at -15°C was preferable to storage in acetone. The latter method was unsatisfactory for electrophoretic analysis since the protein bands obtained lacked sharpness and were poorly resolved.…”
Section: Methodsmentioning
confidence: 99%
“…Apostolakis, 1968;Herlyn, Jantzen, Flaskamp, Hoffmann & von Berswordt-Wallrabe, 1969 Preliminary experiments showed that the storage of human pituitary glands at -15°C was preferable to storage in acetone. The latter method was unsatisfactory for electrophoretic analysis since the protein bands obtained lacked sharpness and were poorly resolved.…”
Section: Methodsmentioning
confidence: 99%